Acquired Cryptorchidism in a 12-Year-old with X-Linked Ichthyosis (XLI) - Hyseni, Fjolla; Guy, Ali; Hyseni, Guri; Kotorri, Breta; Shaipi, Blerona; Aliu, Ermira; Vokshi, Valon; Rakovica, Loran; Mohamed, Essa A; Bajwa, Ibrahim A; et al. (Archives of Clinical and Medical Case Reports, 2021)
Cryptorchidism is a broad term encompassing several distinct entities. True, false cryptorchidism and ectopia testis are congenital disorders. Rarely, cryptorchidism has acquired character. Testicular ascent is also sometimes known as acquired cryptorchidism with an unclear association. Various extracutaneous abnormalities have been reported in some patients with an increased incidence of testicular cryptorchidism. X-linked ichthyosis is a genetic disorder of keratinization characterized by a generalized desquamation of large, adherent, dark brown scales. Steroid sulfatase (STS) deficiency is one of the causes of ichthyoses. STS genes on the X chromosome is responsible for this disease. Herein we report a case of STS deficiency complicated with an acquired cryptorchidism. A 12-yearold- boy with STS deficiency was referred to our hospital because of emptiness of his right scrotum. In early childhood at 5 years of age his skin was excessively dry and scaly by visible scaling and/or hyperkeratosis of most or all the skin in the lower extremity. The child underwent immediate orchiopexy via a groin approach and the testis was successfully mobilized into the scrotum.